Auditory and Visual Sequence Learning in Humans and Monkeys using an Artificial Grammar Learning Paradigm. (1st October 2018) - Milne, Alice E.; Petkov, Christopher I.; Wilson, Benjamin
Graphical abstract: Highlights: The evolutionary roots of human language as a multisensory system remain unclear. Monkeys and humans were tested using auditory and visual rule-based sequences. Comparable patterns of behavioural responses were seen across modalities. Monkey and human behavior was largely similar, with subtle differences. Primates appear to possess comparable modality-general sequencing mechanisms. Abstract: Language flexibly supports the human ability to communicate using different sensory modalities, such as writing and reading in the visual modality and speaking and listening in the auditory domain. Although it has been argued that nonhuman primate communication abilities are inherently multisensory, direct behavioural comparisons between human and nonhuman primates are scant. Artificial grammar learning (AGL) tasks and statistical learning experiments can be used to emulate ordering relationships between words in a sentence. However, previous comparative work using such paradigms has primarily investigated sequence learning within a single sensory modality. We used an AGL paradigm to evaluate how humans and macaque monkeys learn and respond to identically structured sequences of either auditory or visual stimuli. In the auditory and visual experiments, we found that both species were sensitive to the ordering relationships between elements in the sequences. Moreover, the humans and monkeys produced largely similar response patterns to the visual and auditory sequences, indicating that the sequences are processed in comparable ways across the sensory modalities. These results provide evidence that human sequence processing abilities stem from an evolutionarily conserved capacity that appears to operate comparably across the sensory modalities in both human and nonhuman primates. The findings set the stage for future neurobiological studies to investigate the multisensory nature of these sequencing operations in nonhuman primates and how they compare to related processes in humans.